PENGARUH PARTISIPASI ANGGARAN TERHADAP SENJANGAN ANGGARAN DENGAN KOMITMENT ORGANISASI SEBAGAI VARIABEL MODERATING (Studi Empiris pada Kawasan Industri Maluku) - Belianus Patria Latuheru (Universitas Slamet Riyadi, 2006)
ABSTRACT The relationship between budgetary participation and budgetary slack and relationship between job involvement and budgetary slack has been examined in several accounting studies with conflicting results. The conflicting evidence may reflect the influence of a contingent variable. This study examined influence of organizational commitment as moderating variable in the relationship between budgetary participation and budgetary slack, and influence of organizational commitment as moderating variable in the relationship between job involvement and budgetary slack. This study provides empirical evidence that motivational factors of organizational commitment, job involvement and budgetary participation might be important factor in explaining managers propensities to create budgetary slack. The results indicate that for highly committed managers, budgetary participation is associated with decreased propensity to create budgetary slack. For managers who have low levels of commitment to organization's goals and values, budgetary participation is associated with increased propensity to create budgetary slack. Likewise, for highly committed managers, job involvement is associated with decreased propensity to create budgetary slack. For managers who have low levels of commitment organization's goals and values, job involvement is associated with increased propensity to create budgetary slack. Keywords: budgetary participation, job involvement, organizational commitment, budgetary slack.